Financial Strengths and Weaknesses in Service SME’s in Santa Cruz, Bolivia - Osinaga-Flores, Leny Carol (2024)
The objective of this study focused on identifying the financial strengths and weaknesses of SMEs in the service sector of Santa Cruz, Bolivia, which would serve as a basis for decision making and proposing strategies and the development of effective financial planning. To this end, a quantitative research of descriptive scope was carried out in which financial managers of 38 companies were surveyed based on two dimensions: the presence of financial planning and the functional analysis of the financial area. The findings obtained showed that, for the first dimension, companies do prepare cash flow on a monthly and annual basis, but they did not have internal or external personnel to prepare these financial statements on a recurring basis. Regarding the second dimension, financial strength is specified in the analysis of the trends of the financial statements. Regarding the financial weakness, it is shown that they do not analyze the costs of sales with the expenses and sales made.